Internalisasi Pendidikan Multikultural pada Anak Usia Dini - Junanto, Subar; Fajrin, Latifah Permatasari (Jurnal Pendidikan Anak Usia Dini Undiksha, 2020)
The problem in this research is the rising amount of conflict in society caused by a difference in people’s perspectives. Multicultural education is needed to foster tolerance for early childhood. The purpose of this study is to determine the internalization of multicultural education values in early childhood. This research used a descriptive qualitative approach. This research was conducted at PAUD Insan Kamil Dharma Wanita IAIN Surakarta from December 2019 to April 2020. The research subjects were teachers and class B, while the informants were the headmasters and the teacher of class A. The data were collected by observation, interviews, and documentation. The validity of the data is tested using source and method triangulation. The collected data then analyzed by the stages of data reduction, presentation, and concluding. The result showed that internalization was carried out through three stages. There are a transformation of values, transaction value, and trans-internalization using lecturing method, giving a question-answer method, and demonstration methods. The teacher carries out the internalization process by introducing culture, forms of multicultural education learning activities carried out through the introduction of languages (Arabic, English, and Javanese), culture (traditional clothing), arts (regional dances), field trips (visiting museums) and traditional games. Keywords: Internalization, Multicultural Education, Early Childhood